Counseling on Prevention of Sexual Violence and Bullying at State Elementary School 100 Barru - Safaruddin; A. Ariyadi; Andi Muhammad Ishak Ismail (Yayasan Cendekiawan Digital Indonesia, 2024)
Sexual violence is an act involving sexual coercion or harassment against someone without their consent. Bullying is aggressive behavior that is carried out repeatedly by one individual or a group of individuals with the aim of hurting, degrading, or intimidating the victim. Sexual violence and bullying often occur in school environments. Children and adolescents are vulnerable to being victims or perpetrators of these acts. However, due to the taboo nature of this issue, many cases go unreported so existing statistics may not reflect the true numbers. Sexual violence and bullying in schools have serious impacts on victims, including psychological trauma, anxiety disorders, depression, decreased academic performance, and even a high risk of suicide. An unsafe school environment can also affect the entire student population, hindering their learning and social development. Some factors that contribute to sexual violence and bullying in schools include institutional indifference to reporting and action, lack of awareness and adequate education, power imbalances, detrimental social norms, and negative media influences. Preventing sexual violence and bullying in schools requires collaboration between students, teachers, parents, school staff, and the community. This shared responsibility is essential to protecting children and adolescents from physical and psychological harm. With proper education, social support, and proactive action, we can create safe, inclusive, and supportive school environments for all individuals.